2003
DOI: 10.1038/sj.bjc.6600889
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the cell cycle origins for escape from topotecan action by breast cancer cells

Abstract: The anticancer agent topotecan is considered to be S-phase specific. This implies that cancer cells that are not actively replicating DNA could resist the effects of the drug. The cycle specificity of topotecan action was investigated in MCF-7 cells, using time-lapse microscopy to link the initial cell cycle position during acute exposures to topotecan with the antiproliferative consequences for individual cells. The bioactive dose range (0.5 -10 mM) for 1-h topotecan exposures was defined by rapid drug delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…For our experiments we performed 1 h treatment with up to 10 M TPT that was already reported to be sufficient for trapping TOP1 in MCF7 cells [26]. PJ34 was used at a concentration (5 M) that was capable of inhibiting PARP activity but devoid of cytotoxic effects We found that TPT toxicity was higher when PAR synthesis was strongly reduced by either PARP-1 silencing (HeLa …”
Section: Discussionmentioning
confidence: 97%
“…For our experiments we performed 1 h treatment with up to 10 M TPT that was already reported to be sufficient for trapping TOP1 in MCF7 cells [26]. PJ34 was used at a concentration (5 M) that was capable of inhibiting PARP activity but devoid of cytotoxic effects We found that TPT toxicity was higher when PAR synthesis was strongly reduced by either PARP-1 silencing (HeLa …”
Section: Discussionmentioning
confidence: 97%
“…Agents in this pathway might also be engaged outside G 1 , with a role in cell cycle delays or cell death in S and G 2 -M phases; these are the effects experienced by many BrdUrd-positive cells, which never had a chance to reach G 1 . Feeney et al (13) found that after TPT treatment, p53 expression increased more in S and G 2 -M cells than in G 1 cells, and the high level lasted a long time. There is also evidence of activation of p53-dependent responses outside G 1 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Feeney et al (13) investigated cell cycle effects of TPT by timelapse microscopy. They suggested that cells treated with TPT while in G 1 and S phase were unable to duplicate in 48 h, whereas part of G 2 -M cells could divide.…”
Section: Discussionmentioning
confidence: 99%
“…Cells might vary according to their structure (e.g., growth rate and morphology) and/or behaviour (e.g., invasion and metastasis) [23]. The verification and importance of heterogeneity of these cells is therefore explored using a new mathematical multi-cell compartmental model [24,25] of the interaction between TPT and a population of MCF-7 breast cancer cells [8].…”
Section: The Multi-cell Modelmentioning
confidence: 99%
“…The cancer cells are characterised by a rapid proliferation rate which is paralleled by topoisomerase I activity. Since TPT activity is sensitive to proliferating cells and is S-phase specific [8], cancer cells are more likely to be targeted by the drug due to the increased levels of topoisomerase I.…”
mentioning
confidence: 99%